Menelusuri Citra Orang Madura: Tracing the Image of Madurese - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This paper is concerned with the image of Madurese in Dayak Kanayatn people's mind. This study is dealing with cultural cognition and cultural behavior that applies the perspective of hermeneutic-phenomenology with thick description procedure. It is completed with life history approach. This investigation focuses on knowledge, attitude and practice of the Dayak Kanayatn people in its relation with the Madurese. Knowledge, attitude and practice are the result of cultural processes which are caused by social interaction that signed by contact and communication (compare to Gilin & Gilin via Poerwanto, 1997:40). About the image, Boulding (1972:41-51) writes that image is what one believes to be true (subjective knowledge), includes image of fact and value. The behavior of an individual depends on his images. The image will be changed by the time depends on the reached messages. Not only individual, but every society forms its collective images, that is the shared cultural knowledge. Sontag (1995:7 via Riomandha, 2000:35) emphasizes that the image is a representatior that assumed has distance with the reality. Imaging the Madurese in Dayak Kanayatn people's mind are traced by Dayak Kanayatn people's experiences in their relation with the Madurese. The image emerges, fade, compete and influence the Dayak Kanayatn people's attitude and practice. Specific violence of Madurese's (carok) and conflicts influenced the relation between them, also create the Dayak Kanayatn people are terrified. The image of Madurese apt to do violence is accepted and caused the Dayak Kanayatn people escaped, terrorized themselves, directly debated and figthed to the Madurese. Although there is a good image of Madurese, but it tends to fade. The Dayak and Madurese conflict in 1997 at Salatiga is the climax interaction between them that caused the Madurese has been driven out of the Salatiga and the interaction among them is void. In paradoxical reality, the Dayak Kanayatn people of Salatiga are still terrified because of Madurese's lands and rights are still there as Madurese's representation. Moreover, the government supports this matter. Also, the Dayaks-Madurese conflict in 1997 justifies the image of Madurese apt to do violence because the Madurese are iewed ready to take serious risks for facing the lethal war (baparakng babunuh) rhich is helped by the spirits (kamang). But now, there is no kamang again. Lfter the Dayaks-Madurese conflict in 1997, the Dayak Kanayatn people are till spreading the terror among their members through keeping some idioms at exploit the Madurese's violence (carok), although they conscious that hey are also the possessors of the violence. They are also murderer. But, the eflection of violence experiences on themselves emerges pity and regret that .nable the Dayak Kanayatn people to lead to reconciliation with the Madurese.